Factors influencing extrauterine growth retardation in singleton-non-small for gestational age infants in China: A prospective multicenter study - Ya-Sen Wang; Wei Shen; Fan Wu; Jian Mao; Ling Liu; Yan-Mei Chang; Rong Zhang; Xiu-Zhen Ye; Yin-Ping Qiu; Li Ma; Rui Cheng; Hui Wu; et al. (Pediatrics and Neonatology)
Background: The incidence of extrauterine growth retardation (EUGR) varies considerably in different countries due to the distinct definitions and inclusion criteria of individual studies. Most studies included small for gestational age (SGA) very preterm infants (VPIs), resulting in a higher incidence of EUGR. Experts have suggested the accurate definition of “EUGR” in SGA infants is not “true EUGR”. The postnatal growth curve of multiple premature births also differs from that of singletons. As far as we know, there is no study about relationship between singleton-non-SGA preterm infants and EUGR. Objectives: To analyze the factors influencing EUGR among VPIs who were singleton-non-SGA in China. Methods: A prospective-multicenter study was conducted in 28 hospitals distributed through China from September 2019 to December 2020. The clinical data on singleton-non-SGA among VPIs were divided into EUGR group (n = 692) and non-EUGR group (n = 912). Results: Compared to non-EUGR group, the mean gestational age (GA), mean birth weight (BW) and percentage of BW in Fenton curve in EUGR group were lower (P < 0.001 for all). The incidence of EUGR among distinct GA groups (classifications of GA < 28weeks, 28–28+6 weeks, 29–29+6 weeks, 30–30+6 weeks and 31–31+6 weeks) and distinct BW groups (classifications of BW<1000 g, 1000–1249 g, 1250–1499 g, 1500–1999g and 2000–2500 g) were statistically significant (P = 0.004 and P <.001). Logistic regression analysis indicated that later addition of human milk fortifier (HMF), later attainment of HMF sufficient fortification, later return to BW, more accumulative days of fasting, longer duration of parenteral nutrition, total duration of oxygen support and moderate/severe bronchopulmonary dysplasia (BPD) were risk factors for the development of EUGR in singleton-non-SGA VPIs (P < 0.001, P = 0.002, P < 0.001, P = 0.002, P = 0.017, P = 0.003 and P = 0.002, respectively). The use of full-course antenatal steroids, greater BW as a percentile of the Fenton curve, breastfeeding initiation and faster average velocity of weight growth effectively protected against EUGR (P = 0.008, P < 0.001, P < 0.001 and P < 0.001, respectively). Conclusions: The overall incidence of EUGR was 43.1% among singleton-non-SGA VPIs in China. Raising the full-course antenatal steroids usage, reducing the incidence of moderate and severe BPD, attaching importance to the management of enteral nutrition in VPIs and increasing the weight growth velocity can reduce the incidence of EUGR.